(untitled) (World Bulletin of Public Health, 2026)
Persistent infection with high-risk human papillomavirus (hrHPV) remains the principal etiological factor in cervical carcinogenesis, disproportionately affecting women of reproductive age. Despite the global transition from cytology-based screening to primary HPV testing, challenges remain in distinguishing transient infections from transforming lesions requiring clinical intervention.